Pectoralis major muscle atrophy is associated with mitochondrial energy wasting in cachectic patients with gastrointestinal cancer. Issue 3 (22nd March 2022) - Dolly, Adeline; Lecomte, Thierry; Tabchouri, Nicolas; Caulet, Morgane; Michot, Nicolas; Anon, Benjamin; Chautard, Romain; Desvignes, Yoann; Ouaissi, Mehdi; Fromont‐Hankard, Gaëlle; Dumas, Jean‐François; Servais, Stéphane
Abstract: Background: Cancer cachexia is a multifactorial syndrome characterized by involuntary and pathological weight loss, mainly due to skeletal muscle wasting, resulting in a decrease in patients' quality of life, response to cancer treatments, and survival. Our objective was to investigate skeletal muscle alterations in cachectic cancer patients. Methods: This is a prospective study of patients managed for pancreatic or colorectal cancer with an indication for systemic chemotherapy (METERMUCADIG ‐ NCT02573974). One lumbar CT image was used to determine body composition. Patients were divided into three groups [8 noncachectic (NC), 18 with mild cachexia (MC), and 19 with severe cachexia (SC)] based on the severity of weight loss and muscle mass. For each patient, a pectoralis major muscle biopsy was collected at the time of implantable chamber placement. We used high‐resolution oxygraphy to measure mitochondrial muscle oxygen consumption on permeabilized muscle fibres. We also performed optical and electron microscopy analyses, as well as gene and protein expression analyses. Results: Forty‐five patients were included. Patients were 67% male, aged 67 years (interquartile range, 59–77). Twenty‐three (51%) and 22 (49%) patients were managed for pancreatic and colorectal cancer, respectively. Our results show a positive correlation between median myofibres area and skeletal muscle index ( P =  0.0007). Cancer cachexia was associated with a decrease in MAFbx protein expression ( P <  0.01), a marker of proteolysis through the ubiquitin‐proteasome pathway. Mitochondrial oxygen consumption related to energy wasting was significantly increased (SC vs. NC, P =  0.028) and mitochondrial area tended to increase (SC vs. MC, P =  0.056) in SC patients. On the contrary, mitochondria content and networks remain unaltered in cachectic cancer patients. Finally, our results show no dysfunction in lipid storage and endoplasmic reticulum homeostasis. Conclusions: This clinical protocol brings unique data that provide new insight to mechanisms underlying muscle wasting in cancer cachexia. We report for the first time an increase in mitochondrial energy wasting in the skeletal muscle of severe cachectic cancer patients. Additional clinical studies are essential to further the exploring and understanding of these alterations.